Community-Ecosystem Interaction in East Java: Barriers to Participation and Implications for Natural Resources Policy - Marningot Tua Natalis Situmorang; Linda Noviana; Bunga Cahyaputri (Jurnal Penelitian Pendidikan IPA, 2025)
Despite government intervention, sustainable tourism in East Java faces the challenges of a 19.80% decline in tourist visits and low community participation. This study aims to analyze the level of involvement, identify obstacles, and formulate strategies to improve community participation for the welfare of the local community. Using a qualitative descriptive method, data were collected through in-depth interviews with tourism awareness groups, traders, and ticket officers in tourist areas, as well as through document analysis. We processed the data thematically using Qualitative Data Analysis (QDA) Miner 6.00. The results of the study show that community participation is mostly symbolic, at the level of providing information and consultation. The main contribution of the community is in the form of attendance at tourism awareness posts and basic educational activities, with limited involvement in decision-making. The main obstacles include minimal education, suboptimal cross-sector coordination, and limited access to sustainable tourism services and technology. The proposed strategies include technology-based education, sustainable cadre training, local community empowerment, and strengthening cross-sector collaboration. The key finding of this study is that community participation involves the government, local communities, the private sector, academics, and the media. This research is expected to increase the effectiveness of sustainable tourism and become the basis for community participation policies based on inclusive tourism to improve social welfare.